SHADES OF YESTERYEAR - Nathan Toronto (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
Is the Middle East on a path to regional war? One hundred years after the conclusion of World War I, many of the same factors the preceded wars in Europe seem to be in place in the region today: increased arms sales, social and political unrest, and increasing conscription. This paper examines the similarities and differences between the Middle East today and the Europe of 1914. It also analyzes key variables to develop scenarios that could lead to peace or war in the region.